Paradoxes as learning activities for high school mathematics - Sabado, Federico P. (1979)
This study was undertaken to find out whether paradoxes as learning activities for high school mathematics are accepted favorably by teachers and students. Fifteen paradoxes in mathematics were selected from different sources such as school textbooks, magazines, and pocketbooks. Ten mathematics teachers from four high schools in Laguna were selected to evaluate the worksheets by answering a questionnaire using a 5-point scale. Findings of the study showed that the paradoxes were rated favorably by teachers and students. There was a non-significant correlation between teachers' evaluation and students' evaluation of the worksheets in all four criteria used.